2008
DOI: 10.1097/aln.0b013e31817c02e3
|View full text |Cite
|
Sign up to set email alerts
|

Total Intravenous Anesthesia Including Ketamine versus  Volatile Gas Anesthesia for Combat-related Operative Traumatic Brain Injury

Abstract: Total intravenous anesthesia often including ketamine was not associated with improved neurologic outcome compared with VGA. Multiple confounders limit conclusions that can be drawn from this retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 52 publications
0
23
0
3
Order By: Relevance
“…The percentage of good outcomes (GOS 4-5: moderately disabled to good recovery) was also comparable between the two groups (43.6% versus 41.8%). The only available study that investigated the effect of anaesthetic technique on neurological outcomes after TBI was a retrospective study by Grathwohl et al on combat-related TBI (9). Good neurologic outcomes (GOS 4-5) and decreased mortality were more significantly associated with TIVA than with inhalational anaesthesia (75% versus 54% and 5% versus 16%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of good outcomes (GOS 4-5: moderately disabled to good recovery) was also comparable between the two groups (43.6% versus 41.8%). The only available study that investigated the effect of anaesthetic technique on neurological outcomes after TBI was a retrospective study by Grathwohl et al on combat-related TBI (9). Good neurologic outcomes (GOS 4-5) and decreased mortality were more significantly associated with TIVA than with inhalational anaesthesia (75% versus 54% and 5% versus 16%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using PS Power and Sample Size Calculations software, Version 3.0, based on a previous study by Grathwohl et al that showed significant differences (75% versus 54%) in good neurological outcomes (GOS 4-5) between TIVA and inhalational anaesthesia (9). With an expected improvement of 20%, power of study of 80%, alpha of 0.05 and expected dropout rate of 10%, for each group 55 samples were calculated (total samples 110).…”
Section: Methodsmentioning
confidence: 99%
“…TBI affects approximately 1.4 million individuals annually in the United States and carries annual health care costs that exceed $100 billion. 2 TBI is associated with 50% of all trauma-related deaths leading to refractory intracranial hypertension and herniation. 3 Additionally, one-third of the deaths associated with Operation Iraqi Freedom and the Vietnam conflict were caused by TBI.…”
mentioning
confidence: 99%
“…Secondary brain injuries significantly increase with episodic hypotension, increased intracranial pressure and hypoxia, 4 leading to neuronal death from cerebral edema, ischemia, and acute inflammation. 2 Secondary brain injuries are associated with increased rates of mortality and long-term disability. For every person who dies from a trauma-related injury, three are permanently disabled.…”
mentioning
confidence: 99%
See 1 more Smart Citation